The dustiest post-main sequence stars in the magellanic clouds - Jones, Olivia C.; Hony, Sacha (The astrophysical journal, 2015)
Using observations from the Herschel Inventory of The Agents of Galaxy Evolution (HERITAGE) survey of the Magellanic Clouds (MC), we have found 35 evolved stars and stellar end products that are bright in the far-infrared. These 28 (LMC) and 7 (SMC) sources were selected from the 529 evolved star candidates in the HERITAGE far-infrared point source catalogs. Our source identification method is based on spectral confirmation, spectral energy distribution characteristics, careful examination of the multiwavelength images and includes constraints on the luminosity, resulting in a thoroughly vetted list of evolved stars. These sources span a wide range in luminosity and hence initial mass. We found 13 low- to intermediate-mass evolved stars, including asymptotic giant branch (AGB) stars, post-AGB stars, planetary nebulae, and a symbiotic star. We also identify 10 high mass stars, including 4 of the 15 known B[e] stars in the MC, 3 extreme red supergiants that are highly enshrouded by dust, a Luminous Blue Variable, a Wolf-Rayet star, and two supernova remnants. Further, we report the detection of 9 probable evolved objects which were previously undescribed in the literature. These sources are likely to be among the dustiest evolved objects in the MC. The Herschel emission may either be due to dust produced by the evolved star or it may arise from swept-up interstellar medium material.